A bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants and preparation method thereof

By constructing a composite aerogel material with three-dimensional high pore TiO2 loaded bimetallic MOFs, the problem of limited photocatalytic performance of TiO2 and difficulty in recycling MOFs materials is solved, and efficient degradation of organic pollutants and improved photocatalytic activity is achieved.

CN119746942APending Publication Date: 2025-04-04YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411932993.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing TiO2 photocatalysts have limited photocatalytic properties under visible light, and MOFs materials are difficult to recover and reuse during water treatment.

Method used

By constructing a composite aerogel material with three-dimensional high pore TiO2 loaded bimetallic MOFs, the electronic structure of titanium dioxide is adjusted, the separation efficiency of photogenerated electron-hole pairs is enhanced, and the mechanical properties of the material are improved through supercritical drying.

Benefits of technology

It has achieved efficient degradation of organic pollutants, improved photocatalytic activity and catalytic advanced oxidation functions, and significantly improved the recovery and reusability of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746942A_ABST
    Figure CN119746942A_ABST
Patent Text Reader

Abstract

The present invention relates to the field of photocatalysis technology, and provides a bimetallic MOFs-titanium dioxide composite aerogel for efficiently degrading organic pollutants and a preparation method thereof. It is intended to solve the technical problems that TiO2 has limited photocatalytic performance under visible light, short lifetime of photogenerated electron-hole pairs, low efficiency of photocatalytic reaction, and difficulty in recycling and poor reusability of MOFs powder during water treatment. The composite aerogel includes bimetallic MOFs and titanium dioxide aerogel, wherein the bimetallic MOFs is composed of Fe, Cu metal centers and organic skeleton terephthalic acid. The preparation method includes preparing bimetallic MOFs powder and titanium dioxide sol, mixing by ultrasonic oscillation, filtering and washing to obtain bimetallic MOFs-titanium dioxide wet gel, and finally obtaining block composite aerogel by supercritical drying. The material has high-efficiency photocatalytic activity and catalytic advanced oxidation function, can efficiently remove specific organic pollutants, and has excellent mechanical properties and recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysis, and relates to a bimetallic MOFs-titanium dioxide composite aerogel for efficiently degrading organic pollutants and a preparation method thereof. Background Art

[0002] Organic matter is a typical harmful pollutant in the water environment. Organic pollution comes from a wide range of sources, including industrial sources, domestic sources, agricultural sources, medical wastewater, etc. Organic pollutants are inevitably discharged into the aquatic environment. In recent years, organic pollutants such as antibiotics and endocrine disrupting compounds (EDCs) in wastewater have caused serious environmental pollution risks. In order to degrade organic pollutants in water bodies, research based on advanced redox and photocatalysis mechanisms has emerged in an endless stream. Photocatalysis has the advantages of strong redox ability and green economy, and has broad application prospects in environmental remediation. In order to make it economically feasible, it is extremely necessary to develop new green and efficient photocatalysts. Among many optical materials, TiO2 has been widely used due to its advantages such as non-toxicity, good chemical stability, and resistance to light corrosion. However, the photocatalytic performance of TiO2 under visible light is limited, the lifetime of photogenerated electron-hole pairs is short, and the efficiency of photocatalytic reaction is low. In addition to photocatalytic degradation, advanced oxidation methods also have potential in the treatment of water pollutants. Compared with the traditional Fenton reaction, the sulfate radicals (SO4·) produced by using peroxysulfate as an advanced oxidant have a wider pH range and a longer radical half-life for advanced oxidation. Persulfates such as peroxymonosulfate (PMS) and peroxydisulfate (PDS) have excellent oxidation properties, but the reaction speed is slow in the process of pollutant removal, and it is difficult to achieve ideal results in practical applications.

[0003] Metal-organic framework (MOF) is a microporous material that is self-assembled from a metal center and an organic framework. It has the characteristics of extremely high specific surface area, adjustable pore size, customizable structure and photocatalytic activity, and has good application prospects in the fields of organic reaction catalysis and organic pollutant degradation. Compared with single-component MOF materials, bi-(multi)metallic MOF materials show higher reactivity, stronger conductivity and larger specific surface area due to the synergistic effect between different metals, and have better catalytic effects than single-metallic MOFs materials. In addition, due to the limitations of the crystal structure of MOFs materials, they generally exist in powder form, which makes them difficult to recycle and have poor reusability in the fields of photocatalysis and water treatment.

[0004] The composite material of TiO2 and MOF has a good application prospect in the field of photocatalysis, but so far, the preparation method is limited to coating MOF layer by layer on the surface of TiO2 (Journal of Materials Chemistry A, 2022, 10: 9717-9725), powder composite, etc., and the powder form is not conducive to the recovery and reuse of the catalyst in the actual water treatment process (Catalysis Science & Technology, 2023, 13: 5033-5047). The bimetallic MOFs-titanium dioxide composite aerogel provided by the present invention has the characteristics of efficient degradation and good recyclability through the synergistic effect of multiple components. Summary of the invention

[0005] In view of the above problems, the technical purpose of the present invention is to provide a bimetallic MOFs-titanium dioxide composite aerogel material for efficient degradation of organic pollutants and a preparation method thereof. In order to solve the problem that TiO2 is difficult to respond to visible light, bimetallic MOFs (introducing different metal centers and organic ligands) are introduced to change the electronic structure of titanium dioxide, adjust its electronic band structure, and reduce the band gap, so that it can respond to longer wavelength light (including visible light); at the same time, more electron transmission pathways and separation sites are provided, thereby enhancing the separation efficiency of photogenerated electron-hole pairs and significantly improving the photocatalytic activity of the composite aerogel material.

[0006] The present invention obtains a composite aerogel material by constructing a three-dimensional high-porosity TiO2 loaded bimetallic MOFs, wherein the three-dimensional porous network structure of TiO2 has extremely high porosity and specific surface area, giving the composite material high adsorption; at the same time, the three-dimensional network also enhances the mechanical properties of the material, and the block aerogel material is easier to separate from the aqueous solution, which is convenient for the recovery and reuse of the catalyst. In addition, the three-dimensional porous titanium dioxide is used as both a carrier and a photocatalytic functional body, and is composited with bimetallic MOFs, which, on the one hand, synergistically enhances the catalytic efficiency, and on the other hand, promotes the decomposition of activated persulfate to produce more active free radicals by optimizing the electron transmission path and providing active sites, effectively oxidizing and degrading organic pollutants, and realizing the synergy and optimization of advanced oxidation.

[0007] The present invention provides a bimetallic MOFs-titanium dioxide composite aerogel for efficiently degrading organic pollutants, comprising: bimetallic MOFs, wherein the bimetallic MOFs and the titanium dioxide aerogel are composited to form an integral structure;

[0008] Bimetallic MOFs include a bimetallic center and an organic framework connected to the bimetallic center;

[0009] The bimetallic materials are Fe and Cu respectively;

[0010] The organic framework is terephthalic acid, and the molar ratio of the bimetallic Fe to Cu is 1:(0-2) and is not zero.

[0011] The present invention also provides a method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficiently degrading organic pollutants, comprising:

[0012] A second organic solvent containing terephthalic acid is added to a mixed solution I of a soluble iron salt, a soluble copper salt and an excess of a first organic solvent in a molar ratio, and the volume of the second organic solvent is the same as that of the first organic solvent, so that the terephthalic acid is deprotonated and self-assembled with the iron ions and the copper ions to form a bimetallic MOFs solution, wherein the molar ratio of the soluble metal salt to the terephthalic acid is 1:2 to 1:5, and the mass ratio of the soluble metal salt to the first organic solvent is 1:10 to 1:50;

[0013] The bimetallic MOFs solution is transferred into a polytetrafluoroethylene-lined stainless steel autoclave, subjected to a solvothermal reaction under autogenous pressure, and then cooled naturally;

[0014] The precipitate was collected by centrifugation and washed thoroughly with ethanol and deionized water to remove residual impurities;

[0015] The bimetallic MOFs powder is obtained by vacuum drying at a certain temperature for 10 to 12 hours, filtering, washing and drying, and calcining at a high temperature for a certain period of time;

[0016] An easily hydrolyzable organic titanium source and a third organic solvent are mixed in a volume ratio of 1:2 to form a mixed solution II, and a fourth organic solvent is slowly added dropwise to the mixed solution II to undergo a hydrolysis reaction with water to obtain a titanium dioxide sol; in the titanium dioxide sol, the molar ratio of the organic titanium source, the sum of the third and fourth organic solvents, deionized water, and an acidic pH regulator is 1:20.5:6:1.8.

[0017] Adding the bimetallic MOFs powder to the titanium dioxide sol at a mass ratio of 1:2 to 1:20, fully mixing by ultrasonic oscillation, filtering and washing, and obtaining a bimetallic MOFs-titanium dioxide wet gel;

[0018] The wet gel is supercritically dried in a mold to obtain a blocky bimetallic MOFs-titanium dioxide composite aerogel material.

[0019] In the above scheme, the preparation step of forming the mixed solution includes: adding a third organic solvent to the organic titanium source, placing it on a magnetic stirrer with a rotation speed of 600-1200 rpm at room temperature to fully stir it for 20-40 minutes to obtain a transparent clear solution.

[0020] In the above scheme, the preparation step of the fourth organic solvent includes: taking deionized water, an organic solvent, and an acidic pH regulator in a molar ratio of 1:1.2:0.3 and adding them into a beaker, placing it on a magnetic stirrer with a rotation speed of 600-1200 rpm at room temperature to fully stir it, and obtaining a colorless, transparent, clear solution after 20-40 minutes, which is recorded as the fourth organic solvent.

[0021] In the above scheme, the autogenous pressure is formed by the high pressure autoclave at 100°C to 130°C.

[0022] In the above scheme, the vacuum drying temperature is 80°C to 120°C.

[0023] 7. The method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants according to claim 2, characterized in that the calcination temperature is 300°C to 600°C.

[0024] In the above scheme, the soluble iron salt includes at least one of ferric chloride, ferric perchlorate and ferric nitrate, and the soluble copper salt includes at least one of copper chloride, copper nitrate and copper acetate.

[0025] In the above scheme, the titanium source includes at least one of tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate, titanium tert-butoxide, diethyl titanate and titanium tetrachloride.

[0026] In the above scheme, the first organic solvent includes at least one of N,N-dimethylformamide, N-methylpyrrolidone, N,N-diethylformamide, dimethyl sulfoxide, and deionized water;

[0027] The second organic solvent includes at least one of NN-dimethylformamide, methanol, ethanol and isopropanol;

[0028] The third organic solvent includes at least one of anhydrous ethanol, glacial acetic acid, and deionized water, and the acidic pH regulator includes at least one of dilute hydrochloric acid and glacial acetic acid.

[0029] Because the present invention adopts the above-mentioned technical means, it has the following beneficial effects: a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants and a preparation method thereof are provided, and the prepared composite material is a functional three-dimensional mesh structure titanium dioxide aerogel loaded with bimetallic MOFs for efficient catalytic degradation of organic pollutants. The synergistic effect of bimetallic and titanium dioxide enables it to have excellent photocatalytic activity and catalytic advanced oxidation function at the same time, so as to achieve efficient removal of specific organic pollutants. In addition, the bimetallic MOFs material loaded with a three-dimensional mesh structure of titanium dioxide with a large specific surface area and high porosity has high adsorption performance for specific organic pollutants, provides abundant loading points for functional bimetallic MOFs, and solves the problems of difficulty in recycling and poor reusability of MOFs powder in water treatment. Finally, the supercritical drying method is used to make it have excellent mechanical properties in the fields of water treatment and photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Flow chart for the preparation of bimetallic MOFs-titanium dioxide composite aerogels.

[0031] Figure 2 This is the efficiency diagram of bimetallic MOFs-titanium dioxide composite aerogel for the degradation of bisphenol A.

[0032] Figure 3 This is a graph showing the efficiency of bimetallic MOFs-titanium dioxide composite aerogel for tetracycline degradation. DETAILED DESCRIPTION

[0033] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.

[0034] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.

[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0036] The present invention provides a bimetallic MOFs-titanium dioxide composite aerogel for efficiently degrading organic pollutants, wherein the bimetallic MOFs comprises: a bimetal and an organic skeleton, the bimetal is connected to the organic skeleton, and finally composited with a three-dimensional structured titanium dioxide aerogel.

[0037] Furthermore, the organic skeleton is terephthalic acid, and the bimetallics are Fe and Cu respectively.

[0038] Furthermore, the molar ratio of the bimetallic Fe to Cu is 1:(0-2) and is not zero.

[0039] A method for preparing the aforementioned bimetallic MOFs-titanium dioxide composite aerogel comprises:

[0040] A soluble iron salt, a soluble copper salt and a first organic solvent (in excess) are mixed to obtain a mixed solution. A second organic solvent containing terephthalic acid (in the same volume as the first organic solvent) is added to the mixed solution to obtain a bimetallic MOFs solution, wherein the molar ratio of the soluble metal salt to the terephthalic acid is 2:1;

[0041] The bimetallic MOFs solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and after a solvothermal reaction under autogenous pressure for a certain period of time, it is naturally cooled, and the precipitate is collected by centrifugation, and thoroughly rinsed with ethanol and deionized water to remove residual impurities, and then vacuum dried at a certain temperature for 10 to 12 hours. After filtering, washing and drying, the bimetallic MOFs powder is obtained after high temperature calcination for a certain period of time;

[0042] An easily hydrolyzable organic titanium source is mixed with a third organic solvent (volume ratio of 1:2) to prepare a mixed solution, and a fourth organic solvent containing an organic solvent, an acidic pH regulator, an organic framework and deionized water is dropped into the solution to cause a hydrolysis reaction to obtain a titanium dioxide sol. In the titanium dioxide sol, the molar ratio of the organic titanium source, the organic solvent, the deionized water and the acidic pH regulator is 1:20.5:6:1.8.

[0043] The preparation step of the fourth organic solvent comprises: taking deionized water, an organic solvent and an acidic pH regulator respectively with a rubber-tipped dropper and adding them into a beaker, placing them on a magnetic stirrer with a rotation speed of 600 to 1200 rpm under room temperature conditions to fully stir them, and obtaining a colorless, transparent and clear solution after 20 to 40 minutes, which is recorded as the fourth organic solvent, wherein the molar ratio of the deionized water, the organic solvent and the acidic pH regulator is 1:1.2:0.3.

[0044] The bimetallic MOFs powder is added to the sol, ultrasonically vibrated and fully mixed, filtered and washed to obtain a bimetallic MOFs-titanium dioxide wet gel;

[0045] The wet gel is placed in a mold and subjected to supercritical drying to obtain a blocky bimetallic MOFs-titanium dioxide composite aerogel.

[0046] Furthermore, the wet gel is placed in a mold and subjected to supercritical drying steps:

[0047] S1. Open the lid of the drying kettle of the 2L multi-purpose supercritical test device, place the bimetallic MOFs-titanium dioxide wet gel in it, add an appropriate amount of anhydrous ethanol to completely submerge it, and then seal the drying kettle, open the valve switch of the gas cylinder, and the gas cylinder contains a supercritical fluid.

[0048] S2. Open the air inlet valve of the drying kettle and start to slowly intake air. The air intake rate increases by about 0.1-0.2MPa every 10s. When the pressure of the drying kettle and the pressure of the liquid tank are the same, fully open the air inlet valve and turn on the heating switch to heat the kettle.

[0049] S3. When the temperature at the top of the kettle reaches the preset temperature of 25℃~60℃, turn on the gas booster pump, set the flow rate to 20, and start pressurizing the drying kettle.

[0050] S4. When the pressure of the drying kettle reaches 10MPa~12MPa, open the drying kettle pressure regulating valve and the separation kettle I pressure regulating valve, and slowly open the pressure regulating back pressure valve to circulate the supercritical fluid.

[0051] S5. Keep the pressure in the kettle between 10MPa and 15MPa, and close the gas booster pump and all inlet and outlet valves after 40min to 60min.

[0052] S6. Repeat the process of S4 3 to 5 times

[0053] S7. Close the gas cylinder, set the temperature in the kettle to 20℃~30℃, open the direct exhaust valve of the drying kettle, and wait until the pressure in the kettle reaches 0.1~0.2MPa, then open the kettle cover and take out the sample to obtain a block-shaped bimetallic MOFs-titanium dioxide aerogel composite material.

[0054] Further, the autogenous pressure is formed by the autoclave at 100°C to 130°C;

[0055] Furthermore, the vacuum drying temperature is 80°C to 120°C.

[0056] Furthermore, the calcination temperature is 300°C to 600°C.

[0057] Furthermore, the solvent thermal reaction time is 24h to 36h;

[0058] Further, the detergent is anhydrous ethanol;

[0059] Furthermore, the soluble iron salt includes at least one of ferric chloride, ferric perchlorate and ferric nitrate. The soluble copper salt includes at least one of copper chloride, copper nitrate and copper acetate.

[0060] Furthermore, the titanium source includes at least one of tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate, titanium tert-butoxide, diethyl titanate and titanium tetrachloride.

[0061] Further, the first organic solvent includes at least one of N,N-dimethylformamide, N-methylpyrrolidone, NN-diethylformamide, and dimethyl sulfoxide; the second organic solvent includes at least one of N,N-dimethylformamide, methanol, ethanol, and isopropanol. The third organic solvent includes at least one of anhydrous ethanol, glacial acetic acid, and deionized water. The acidic pH regulator includes at least one of dilute hydrochloric acid and glacial acetic acid.

[0062] Example 1

[0063] S1: Use a rubber-tipped dropper to take 10 mL of butyl titanate and dissolve it in 22 mL of anhydrous ethanol. Place it on a magnetic stirrer at a speed of 900 rpm at room temperature to stir it thoroughly. After 20 minutes, a light yellow transparent clear solution is obtained, which is recorded as mixed solution 1.

[0064] S2: Use a rubber-tipped dropper to take 3.3 mL of deionized water, 12 mL of anhydrous ethanol, 3 mL of glacial acetic acid, and 1 mL of N,N-dimethylformamide and add them to another beaker. Place it on a magnetic stirrer at 900 rpm at room temperature to stir it thoroughly. After 20 minutes, a colorless, transparent, clear solution was obtained, which was recorded as mixed solution 2.

[0065] S3: Use a rubber-tipped dropper to draw mixed solution 2 and add it dropwise into mixed solution 1 at a dropping rate of 1 mL / min. Stir it to fully hydrolyze it to obtain a uniform and transparent TiO2 sol. Irradiation with a red laser pen will produce the Tyndall effect, indicating that the TiO2 wet gel was successfully prepared.

[0066] S4-1: 6.67 mmol FeCl3·6H2O (1.798 g) and 3.33 mmol Cu(NO3)2·3H2O (0.807 g) were dissolved in 30 mL DMF solution, and then 30 mL DMF solution containing 5 mmol H2BDC (0.830 g) was slowly added under magnetic stirring.

[0067] S4-2: The mixed solution was stirred continuously for 30 min and then transferred into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave for a solvothermal reaction at 110 °C under autogenous pressure for 36 h.

[0068] S4-3: After natural cooling, the precipitate was collected by centrifugation, thoroughly rinsed with ethanol and deionized water to remove residual impurities, and dried under vacuum at 80 °C for 12 h.

[0069] S4-4: The precipitate was placed in a tube furnace and annealed in flowing argon at 450°C for 2 hours (heating rate 5°C min -1 ), and calcined to obtain bimetallic MOFs powder.

[0070] S5: Add the bimetallic MOFs powder to the TiO2 wet gel and stir evenly. After the wet gel is left to stand for 2 hours at room temperature, gelation is completed to obtain a mixed gel. Soak it in anhydrous ethanol, the liquid level of which is about 2 cm higher than the upper surface of the gel, and replace it every 24 hours. Repeat this step 3 to 4 times to fully replace the residual water and organic matter in the gel, and then perform supercritical drying.

[0071] S6: Supercritical drying process of mixed gel

[0072] S6-1: Place the replaced TiO2 wet gel in the drying kettle of the supercritical drying device and add an appropriate amount of anhydrous ethanol to completely submerge it.

[0073] S6-2: Seal the lid of the supercritical drying reactor, close all valves and turn on the power.

[0074] S6-3: Connect the CO2 cylinder pressure reducing valve to the air inlet pipe of the equipment, and then open the CO2 cylinder valve switch.

[0075] S6-4: Open the air inlet valve of the drying kettle and start to slowly intake air at a rate of 0.1MPa every 10s. When the pressure of the drying kettle is the same as the pressure in the liquid tank, fully open the air inlet valve and turn on the heating switch to heat the kettle.

[0076] S6-5: When the top temperature of the kettle reaches the preset temperature of 45°C, turn on the supercritical drying CO2 booster pump, set the flow rate to 20, and start pressurizing the drying kettle.

[0077] S6-6: When the pressure of the drying kettle reaches 12MPa, the kettle reaches a supercritical state. Open the drying kettle pressure regulating valve and the separation kettle I pressure regulating valve, and slowly open the pressure regulating back pressure valve to circulate the CO2 gas.

[0078] S6-7: Keep the pressure in the kettle at 12MPa, remove the anhydrous ethanol in the drying kettle within one hour, and finally close the CO2 booster pump and all inlet and outlet valves to maintain the pressure.

[0079] S6-8: Repeat step S66 five times to ensure that the solvent in the mixed gel is fully extracted and discharged by the CO2 gas.

[0080] S6-9: Close the gas cylinder, set the temperature in the kettle to 40°C, open the direct exhaust valve of the drying kettle to slowly discharge the CO2 gas from the drying kettle, and open the lid of the kettle to take out the sample when the pressure in the kettle reaches 0.1MPa to obtain a bulk bimetallic MOFs-titanium dioxide aerogel composite material.

[0081] Example 2

[0082] The preparation method of bimetallic MOFs-titanium dioxide composite aerogel is the same as that of Example 1, except that 3.33 mmol FeCl3·6H2O and 6.67 mmol Cu(NO3)2·3H2O are added.

[0083] Example 3

[0084] The preparation method of bimetallic MOFs-titanium dioxide composite aerogel is the same as that of Example 1, except that 5 mmol FeCl3·6H2O and 5 mmol Cu(NO3)2·3H2O are added.

[0085] Example 4

[0086] The preparation method of bimetallic MOFs-titanium dioxide composite aerogel is the same as that of Example 1, except that the calcination temperature of the precipitate in the tubular furnace is 300°C.

[0087] Example 5

[0088] The preparation method of bimetallic MOFs-titanium dioxide composite aerogel is the same as that of Example 1, except that the calcination temperature of the precipitate in the tubular furnace is 600°C.

[0089] Bisphenol A solution (0.1mM) and tetracycline solution (0.1mM) were prepared. Each group of experiments was conducted in 100mL of BPA solution. The pH of the solution was adjusted to 4.5 with diluted hydrochloric acid and sodium hydroxide solution. 10mg of catalyst and 10mL of potassium persulfate solution were added to each experimental group, and stirring was continued under the illumination of a 300W xenon lamp (λ>420nm). After 25min of reaction, 1mL of sample was taken out and the pollutant concentration was detected on a high performance liquid chromatography-mass spectrometer. The test results are shown in Table 1.

[0090] Table 1

[0091]

[0092] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants, characterized in that: It includes: bimetallic MOFs, wherein the bimetallic MOFs and titanium dioxide aerogel are composited to form an integral structure; Bimetallic MOFs include a bimetallic center and an organic framework connected to the bimetallic center; The bimetallic materials are Fe and Cu respectively; The organic framework is terephthalic acid, and the molar ratio of the bimetallic Fe to Cu is 1:(0-2) and is not zero.

2. A method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants according to claim 1, characterized in that: include: A second organic solvent containing terephthalic acid is added to a mixed solution I of a soluble iron salt, a soluble copper salt and a first organic solvent in a molar ratio, and the volume is the same as that of the first organic solvent, so that the terephthalic acid is deprotonated and self-assembled with the iron ions and the copper ions to form a bimetallic MOFs solution, wherein the molar ratio of the soluble metal salt to the terephthalic acid is 1:2 to 1:5, and the mass ratio of the soluble metal salt to the first organic solvent is 1:10 to 1:50; The bimetallic MOFs solution is transferred into a polytetrafluoroethylene-lined stainless steel autoclave, subjected to a solvothermal reaction under autogenous pressure, and then cooled naturally; The precipitate was collected by centrifugation and washed thoroughly with ethanol and deionized water to remove residual impurities; The bimetallic MOFs powder is obtained by vacuum drying at a certain temperature for 10 to 12 hours, filtering, washing and drying, and calcining at a high temperature for a certain period of time; An easily hydrolyzable organic titanium source and a third organic solvent are mixed in a volume ratio of 1:2 to form a mixed solution II, and a fourth organic solvent is slowly added dropwise to the mixed solution II to undergo a hydrolysis reaction with water to obtain a titanium dioxide sol; in the titanium dioxide sol, the molar ratio of the organic titanium source, the sum of the third and fourth organic solvents, deionized water, and an acidic pH regulator is 1:20.5:6:1.

8. The bimetallic MOFs powder is added to the titanium dioxide sol at a mass ratio of 1:2 to 1:20, fully mixed by ultrasonic oscillation, filtered and washed to obtain a bimetallic MOFs-titanium dioxide wet gel; The wet gel is supercritically dried to obtain a blocky bimetallic MOFs-titanium dioxide composite aerogel material.

3. The method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficiently degrading organic pollutants according to claim 2, characterized in that: The preparation steps for forming the mixed solution include: adding a third organic solvent to an organic titanium source, placing the mixture on a magnetic stirrer with a rotation speed of 600 to 1200 rpm at room temperature to fully stir the mixture for 20 to 40 minutes to obtain a transparent clear solution.

4. The method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants according to claim 2, characterized in that: The preparation step of the fourth organic solvent includes: adding deionized water, an organic solvent, and an acidic pH regulator into a beaker in a molar ratio of 1:1.2:0.3, placing the beaker on a magnetic stirrer at a rotation speed of 600 to 1200 rpm under room temperature to fully stir the beaker, and obtaining a colorless, transparent, clear solution after 20 to 40 minutes, which is recorded as the fourth organic solvent.

5. The method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants according to claim 2, characterized in that: The autogenous pressure is formed by the autoclave at 100°C to 130°C.

6. The method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants according to claim 2, characterized in that: The vacuum drying temperature is 80°C to 120°C.

7. The method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants according to claim 2, characterized in that: The calcination temperature is 300°C to 600°C.

8. The method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants according to claim 2, characterized in that: The soluble iron salt includes at least one of ferric chloride, ferric perchlorate and ferric nitrate, and the soluble copper salt includes at least one of copper chloride, copper nitrate and copper acetate.

9. The method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants according to claim 2, characterized in that: The titanium source includes at least one of tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate, titanium tert-butoxide, diethyl titanate and titanium tetrachloride.

10. The method for preparing a bimetallic MOFs-titanium dioxide composite aerogel for efficient degradation of organic pollutants according to claim 2, characterized in that: The first organic solvent includes at least one of N,N-dimethylformamide, N-methylpyrrolidone, N,N-diethylformamide, dimethyl sulfoxide, and deionized water; The second organic solvent includes at least one of N,N-dimethylformamide, methanol, ethanol and isopropanol; The third organic solvent includes at least one of anhydrous ethanol, glacial acetic acid, and deionized water, and the acidic pH regulator includes at least one of dilute hydrochloric acid and glacial acetic acid.